Violence Against Women in Pakistan: A Forensic Discourse Analysis of Honour Killings in The Dawn - Mehr un Nisa; Shahzeb Shafi*; Iqra Maryam Qandeel Arif; Alvina Imdad (Al-Qanṭara, 2022)
The brutal custom of honour killings is practised in various societies of the world, including Pakistan; thereupon, the underline objectives of such killings are explored in a famous Pakistani Newspaper, ‘The Dawn’. Two (2) editorials from ‘The Dawn’ newspaper were analysed using a text analysis technique comprising vocabulary, grammar, cohesion and text structure called Forensic Discourse Analysis (FDA). The basic descriptive mixed-method revealed that The Dawn’s left-wing ideology influences people, and the patterns of honour killings are usually socially and economically constructed with the strong support of flawed frames of culture and religion, favouring the culprits with the sympathetic escape. Keywords: Honour Killings, The Dawn, Forensic Discourse Analysis (FDA), Pakistan, Textual Analysis.